Tryptophan degradation by human placental indoleamine 2,3-dioxygenase regulates lymphocyte proliferation. - Kudo, Y; Boyd, C; Sargent, I; Redman, C (2001)
1. The physiological importance of human placental indoleamine 2,3-dioxygenase (EC 1.13.11.42), the first and rate-limiting enzyme in tryptophan metabolism, in regulating feto-maternal immunology has been studied. 2. Concentrations were measured in placental villous explant conditioned media of 14 amino acids that are known to be required for lymphocyte proliferation. In the absence of interferon-gamma only tryptophan and threonine were significantly lowered; in the presence of interferon-gamma (known to stimulate indoleamine 2,3-dioxygenase) tryptophan but not threonine depletion was much greater. 3. Peripheral blood mononuclear cell proliferation determined by measuring thymidine incorporation into DNA following culture in the medium previously conditioned by culture of villous explants was markedly reduced when placental indoleamine 2,3-dioxygenase was stimulated with interferon-gamma. Inhibition of placental indoleamine 2,3-dioxygenase by 1-methyl-tryptophan prevented inhibition of thymidine incorporation. Supplementation of the conditioned medium with tryptophan but no other amino acid completely reversed the inhibition of thymidine incorporation. 4. Flow cytometric analysis showed that CD4-positive T lymphocyte division was specifically suppressed by indoleamine 2,3-dioxygenase-mediated tryptophan depletion. This inhibition of T cell proliferation was due to arrest of cell cycle progression. 5. To study the mechanism of tryptophan sensing we examined the ability of 11 L-tryptophan analogues to support lymphocyte proliferation. Only L-tryptophan methyl and ethyl esters were able to stimulate proliferation in tryptophan-free media. Since both of these molecules are readily degraded to tryptophan by intracellular esterases this suggests that the tryptophan sensor is intracellular. 6. Our results show that mechanisms are present in the human placenta which are able to regulate cellular proliferation of the maternal immune system. This mechanism is dependent both on placental indoleamine 2,3-dioxygenase-mediated tryptophan degradation and on tryptophan sensing systems within lymphocytes.